Advances in Thin Film Technology for Flexible Display Applications - Fatima Azzahra; Dina Ahmed; Mai Kamal (Yayasan Adra Karima Hubbi, 2024)
The rapid growth of flexible display technologies has spurred significant advancements in thin film technology. These innovations are crucial for developing lightweight, durable, and versatile display solutions that can be integrated into various applications, from consumer electronics to wearable devices. This study aims to investigate recent advancements in thin film technologies specifically tailored for flexible display applications. The focus is on identifying key materials and fabrication techniques that enhance performance and flexibility. A comprehensive review of current literature was conducted, analyzing various thin film materials, including organic light-emitting diodes (OLEDs), organic photovoltaics (OPVs), and flexible substrates. The performance metrics of these materials were evaluated based on criteria such as flexibility, transparency, and electrical conductivity. The findings reveal that the integration of novel materials, such as graphene and silver nanowires, significantly improves the electrical and mechanical properties of thin films. Enhanced flexibility and durability were observed in displays utilizing these advanced materials, leading to improved performance in real-world applications. This research highlights the critical role of thin film technology in advancing flexible display applications. The integration of innovative materials and techniques is essential for overcoming current limitations, paving the way for the next generation of flexible and efficient display solutions. Continued exploration in this field will drive further innovations and expand the potential applications of flexible displays.